Long-term follow-up experience in anal canal cancer treated with Intensity-Modulated Radiation Therapy: Clinical outcomes, patterns of relapse and predictors of failure. (March 2020) - de Meric de Bellefon, Maïlys; Lemanski, Claire; Castan, Florence; Samalin, Emmanuelle; Mazard, Thibault; Lenglet, Alexis; Demontoy, Sylvain; Riou, Olivier; Llacer-Moscardo, Carmen; Fenoglietto, Pascal; Aillères, Norbert; Thezenas, Simon; et al.
Highlights: IMRT for anal cancer is efficient in the long-term with manageable toxicity. Advanced T-stage remains the main prognostic factor for survival. Planned gaps and prolonged treatment breaks should be avoided. Locoregional failures mostly occur in-field suggesting radioresistance. Novel systemic strategies are needed to improve distant control. Abstract: Background and purpose: To assess the long-term outcomes of patients with squamous cell carcinoma of the anal canal (SCCAC) treated with Intensity-Modulated Radiation Therapy (IMRT). Material and methods: From 2007 to 2015, 193 patients were treated by IMRT for SCCAC. Radiotherapy delivered 45 Gy in 1.8 Gy daily-fractions to the primary tumor and elective nodal areas, immediately followed by a boost of 14.4–20 Gy to the primary tumor and involved nodes. Concurrent chemotherapy with 5-FU-mitomycin (MMC) or cisplatin was added for locally advanced tumors. Survivals were estimated by Kaplan–Meier method. Locoregional (LR) relapses were precisely assessed. Prognostic factors were evaluated by uni- and multivariate analyses. Late toxicity was scored according to the Common Toxicity Criteria for Adverse Events v4.0. Results: Median follow-up was 70 months (range, 1–131). Forty-nine men (25%) and 144 women (75%) were analyzed. Median age was 62 years. Tumor stages were I, II, III and IV in 7%, 24%, 63% and 6% of cases, respectively. Chemotherapy was delivered in 167 patients (87%), mainly MMC (80%). Five-year OS, DFS, CFS and LR control rates were 74%, 68%, 66% and 85%, respectively. Forty-one patients (21%) had a relapse: 22 were LR, mostly in-field (68%). Predictors for LR failure were exclusive radiotherapy, chemotherapy lacking MMC and treatment breaks >3 days. Overall late toxicity ≥grade 2 occurred in 43% of patients, with 24% grade 3 and one case of grade 4 (hematuria). Conclusion: CRT with IMRT assures excellent local control in locally advanced SCCAC with manageable long-term toxicity. Multicentric prospective trials are required to reinforce those results.